Leafhopper genus Kolla Distant (Hemiptera: Cicadellidae: Cicadellinae) with descriptions of four new species from China - Feng, Ling; Zhang, Yalin (Zootaxa, 2015)
Four new species of the genus Kolla from China, Kolla emphysematosa, K. prolongata, K. procerula and K. petalina spp. nov. are described and illustrated. A key to the males of Chinese species and a checklist of the known species worldwide are provided.